Samuel Irwin, Reports of Cases At Law And In Chancery 566 (vol. #278, Chicago, Ill, 1917) - (:unkn) unknown (General Publisher, 1917)
Court issued opinion reciting chapter 54 of the Chicago code of 1911, where an ordinance granted the general superintendent of the police the authority to refuse a license to those not considered "the People" of the time, namely persons having been convicted of a crime and minors. The licenses concerned buying, selling, or otherwise transferring pistols, revolvers, derringers, Bowie-knives, dirk, other weapons of like character.
--
Keywords: TRANSFER & POSSESSION